Ethanolic Extract of Alternanthera Sessilis: A Potential Therapeutic Agent for Behavioral Improvements in Reserpine-Induced Parkinsonian Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The present study evaluated the potential of an ethanol extract from Alternanthera sessilis to alleviate reserpine-induced Parkinson's disease (PD) like behavioural manifestations in rats. The animals were grouped into five: a control group, a group receiving only reserpine, a group treated with levodopa and carbidopa, and two groups given different doses of the Alternanthera sessilis extract. Reserpine was used to mimic PD symptoms, while the extract was administered orally at two different concentrations. The behavioral tests were conducted to assess locomotor activity, grip strength, catalepsy, and rearing activity. Locomotor activity was measured using an actophotometer, where interruptions in light beams caused by the rates were recorded over a 10-minute period. Grip strength was evaluated using a rotarod apparatus, measuring the time taken for rats to fall off individual rods. Catalepsy was assessed through a bar test, measuring the time for rats to descend from a horizontal bar to the base. Rearing activity was observed in a round open field arena, with parameters including the occurrence rate of rearing, general movements score, and duration spent in the center of the arena. The results revealed administration of reserpine led to a decrease in body weight, locomotor activity, muscle coordination, catalepsy score, rearing activity, and grip strength compared to the control group. Conversely, treatment with levodopa and carbidopa resulted in increased values for these parameters. Importantly, administration of Alternanthera sessilis extract showed a dose-dependent reversal of the effects induced by reserpine, with significant increases observed in body weight, locomotor activity, muscle coordination, rearing activity, general movement, and grip strength, indicating its potential therapeutic effects. In conclusion, the present study results suggest that the extract from the Alternanthera sessilis plant might protect brain cells and improve symptoms of Parkinson's disease. However, more research is needed to understand how it works and if it can be used safely and effectively clinical trails.